Investment Nationalism Value in Children Age 5-6 Years Reviewed from Application of Media Papan Jodoh Pancasila in TKIT Al-Husna Mayong Jepara District - Wulandari, Devita; Windiarti, Rina (Jurusan PGPAUD FIP UNNES, 2017)
The pluralism of the Unitary State of the Republic of Indonesia often creates various problems in the layers of society. Like the many frequent anarchic acts, there are many racial, ethnic and religious conflicts. This all resulted in a diminishing sense of national unity and unity. The Indonesian people forget who he really is, who should live on the basis of Pancasila. The purpose of this research is to obtain empirical data about the cultivation of the value of nationalism in children aged 5-6 years in terms of the application of media papan jodoh pancasila in TKIT Al-Husna, Mayong Subdistrict, Jepara District. The type of research used is (experimental research ). Sampling technique in this research is totality sampling (sample saturated). The sample in this research is 30 children. Methods of data collection in this study are observation, documentation and Likert scale use of nationalism value investing. The result of calculation based on test Paired Sample t Test obtained value-t table> t arithmetic> t table that is (-2.045> -16.434 or 16.434> 2.045), with sig = 0.000, so Ho rejected and Ha accepted means there are significant differences in planting the value of nationalism in children aged 5-6 years after applying the board media podasila pancasila. The significant difference can be seen from the sig value of 2 tailed <0,05 ie 0.000. It can also be seen from the average value obtained before and after the media applied pancasila board mate that is 107.63 to 136.27 So that an increase in score of 28.64.